KEPRAKTISAN BUKU ILMIAH POPULER ETNOBOTANI TUMBUHAN OBAT DI KOTA TIDORE KEPULAUAN - Juniartin, Juniartin; Matdoan, Muhamad; Lasamida, Aswini (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The importance of traditional knowledge about medicinal plants needs to be documented in the form of references through scientific research so that it is not lost by cultural modernization so that it can be preserved by the next generation. Written references about traditional knowledge of medicinal plants can be written in the form of books, one of which is popular scientific books. The purpose of this research is to develop a popular scientific book on medicinal plants in the city of Tidore Islands. The type of research used is research and development with the ADDIE development model consisting of 5 stages, namely analysis, design, development, implementation, evaluation. The research subjects consisted of 12 students in the 3rd semester of the Biology study program, 3 students in the 5th semester of the Biology study program, and 4 people from the community who represented the city of Tidore. The data collection technique uses a validation questionnaire for experts and small-scale trials. The results of the development of popular scientific books show that the average results of the validation and testing are in the appropriate category for use with good predicates in accordance with the table of eligibility criteria and product revisions.